2022
DOI: 10.1002/jum.16037
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Two‐Dimensional Ultrasound Evaluation as a Screening Tool for Levator ani Muscle Avulsion in Postpartum Women

Abstract: Objectives-To evaluate the agreement between two-dimensional transvaginal ultrasound (2D-TVUS) and transperineal tomographic ultrasound imaging on three-dimensional (3D) volume in diagnosing levator ani muscle (LAM) avulsion of postpartum women. Furthermore, we tested the repeatability of the 2D-TVUS in measuring the LAM thickness.Methods-A retrospective study was performed using the data sets from postpartum women. One doctor measured the thickness of the LAM on the images at the attachment to the arcus tendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…[36][37][38] Hence, the early diagnosis of LAM after childbirth is important, even when screening techniques are applied. 39 In our study, the detection of LAM avulsion was shown to be especially useful in the case of postmenopausal patients, improving the diagnostic capacity achieved by only the difference in the pubis-uterine fundus distance at rest and with the Valsalva maneuver. We believe it is possible that LAM avulsion and injuries of the uterosacral-cardinal ligament complex can occur in most cases at the same time and for the same cause (vaginal delivery).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…[36][37][38] Hence, the early diagnosis of LAM after childbirth is important, even when screening techniques are applied. 39 In our study, the detection of LAM avulsion was shown to be especially useful in the case of postmenopausal patients, improving the diagnostic capacity achieved by only the difference in the pubis-uterine fundus distance at rest and with the Valsalva maneuver. We believe it is possible that LAM avulsion and injuries of the uterosacral-cardinal ligament complex can occur in most cases at the same time and for the same cause (vaginal delivery).…”
Section: Discussionmentioning
confidence: 66%
“…The relationship that exists between pregnancy, childbirth, and changes in the pelvic floor has been described by different authors, 34,35 determining an association between LAM avulsion and prolapse symptoms 36–38 . Hence, the early diagnosis of LAM after childbirth is important, even when screening techniques are applied 39 . In our study, the detection of LAM avulsion was shown to be especially useful in the case of postmenopausal patients, improving the diagnostic capacity achieved by only the difference in the pubis‐uterine fundus distance at rest and with the Valsalva maneuver.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 2D-TPUS can be executed readily using any convex transducer and requires less expertise and training compared with 3D-TPUS. Although certain studies have hinted at the potential of 2D-TPUS as a promising technique in evaluating LAM integrity 44,45 , the only LAM hiatal dimension measured on 2D-TPUS reported to date is the anteroposterior diameter 4,36,37 . Based on our findings, we propose that 2D-and 3D-TPUS methods can be used interchangeably for measuring LAM hiatal TD.…”
Section: Discussionmentioning
confidence: 99%